Uncle GOOGLE Has a Choir Rehearsal Today – About Ludical Technics of Introducing and Consolidating Vocabulary During Foreign Language Classes - Sroka, Jakub (Ludicity in (Glotto)Didactic, 2020)
The article presents the ludic technics the author uses during introducing and consolidating vocabulary in a foreign language classes. It provides a description of what these methods are about, how they were created, under what circumstances they could be used and what didactics could achieve thanks to them. The Conclusions show relevant reflections about using several introducing and consolidating vocabulary technics, comments and suggestions for teachers that will help them in the implementation task with the use of chosen methods.